Harm reduction, methadone maintenance treatment and the root causes of health and social inequities: An intersectional lens in the Canadian context - Varcoe Colleen; Browne Annette J; Smye Victoria; Josewski Viviane (BMC, 2011)
Abstract Background Using our research findings, we explore Harm Reduction and Methadone Maintenance Treatment (MMT) using an intersectional lens to provide a more complex understanding of Harm Reduction and MMT, particularly how Harm Reduction and MMT are experienced differently by people dependent on how they are positioned. Using the lens of intersectionality, we refine the notion of Harm Reduction by specifying the conditions in which both harm and benefit arise and how experiences of harm are continuous with wider experiences of domination and oppression; Methods A qualitative design that uses ethnographic methods of in-depth individual and focus group interviews and naturalistic observation was conducted in a large city in Canada. Participants included Aboriginal clients accessing mainstream mental health and addictions care and primary health care settings and healthcare providers; Results All client-participants had profound histories of abuse and violence, most often connected to the legacy of colonialism (e.g., residential schooling) and ongoing colonial practices (e.g., stigma & everyday racism). Participants lived with co-occurring illness (e.g., HIV/AIDS, Hepatitis C, PTSD, depression, diabetes and substance use) and most lived in poverty. Many participants expressed mistrust with the healthcare system due to everyday experiences both within and outside the system that further marginalize them. In this paper, we focus on three intersecting issues that impact access to MMT: stigma and prejudice, social and structural constraints influencing enactment of peoples' agency, and homelessness; Conclusions Harm reduction must move beyond a narrow concern with the harms directly related to drugs and drug use practices to address the harms associated with the determinants of drug use and drug and health policy. An intersectional lens elucidates the need for harm reduction approaches that reflect an understanding of and commitment to addressing the historical, socio-cultural and political forces that shape responses to mental illness/health, addictions, including harm reduction and methadone maintenance treatment.